The Impact of Microfinance Institutions on Women Empowerment in Rajshahi, Bangladesh - Nessa, Tasqurun (2011)
The empowerment of women is one of the central issues in the process of development of all developing countries in the world. This study investigated the empowerment of poor women who participated in group-based credit program in Bangladesh. Studies have shown how women participation in group-based credit program can improve individual and household income. However, limited evidence exists on which type of empowerment is more significant for poor women. It is not known whether economic decision making, household decision making, freedom of movement, ownership of property or political and social awareness is more significant for women. This study is based on household level data collected from 600 poor women in eight districts of Rajshahi division in Bangladesh. This study collected micro-credit borrower data from Grameen Bank, Bangladesh Rural Advancement Committee (BRAC) and Association for Social Advancement (ASA). Five dimensions of women empowerment are used to arrive at the overall empowerment. To measure empowerment, this study used mean value of the five dimensions of empowerment. The findings show that age, family size, area, involvement with Micro Finance Institution (MFI) and loan size are positively correlated and significant with women empowerment. Another important factor such as education is negatively correlated with women empowerment for all women (MFI member and non MFI member). Based on the results of the study it can be concluded that the level of women empowerment of poor women in Bangladesh can be significantly improved by involvement with MFI. It is noted that MFI members have more empowerment than non MFI members, but the level of women empowerment of MFI member is not satisfactory. Higher income increases women’s ability to contribute more to the daily household expenditure, and eventually improve their empowerment. It is recommended that the government and other development organizations should work together in addressing this empowerment issue with better implementation of strategies such as more loans, and proper guide to borrowers. All these strategies can influence the level of empowerment of women in a developing country such as in Rajshahi division, Bangladesh.